2015
DOI: 10.3171/2015.1.peds14575
|View full text |Cite
|
Sign up to set email alerts
|

Transosseous cerebrospinal fluid fistula 14 years after Chiari decompression: presentation and management

Abstract: The authors report a unique case of a transosseous CSF fistula that was detected more than 10 years after treatment of a symptomatic Chiari I malformation. This lesion initially presented as an intraosseous cystic lesion involving the C-2 vertebra, which was found to communicate freely with the subarachnoid space through a tiny dural opening. Surgical management involved hemilaminectomy and repair of the dural defect followed by reinforcement of the bony defect with demineralized bone matrix. Following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
3
1
Order By: Relevance
“…After revision surgery our patient remained asymptomatic and did not require further treatment despite the blockage of 2 potential additional sites of CSF absorption. The difference between our previously reported patient 18 and the patient reported by Gandhoke et al 9 may have been that before the foramen magnum decompression Gandhoke et al's patient had an underlying compensated hydrocephalus that became clinically relevant after the revision surgery and led to an obstruction of the additional CSF absorption pathway that had developed over the years.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…After revision surgery our patient remained asymptomatic and did not require further treatment despite the blockage of 2 potential additional sites of CSF absorption. The difference between our previously reported patient 18 and the patient reported by Gandhoke et al 9 may have been that before the foramen magnum decompression Gandhoke et al's patient had an underlying compensated hydrocephalus that became clinically relevant after the revision surgery and led to an obstruction of the additional CSF absorption pathway that had developed over the years.…”
Section: Discussioncontrasting
confidence: 64%
“…To our knowledge, only 2 patients with intravertebral CSF collections have been reported so far. 9,18 Gandhoke et al 9 first reported a patient with Chiari I malformation who developed a collection of CSF in C2 after foramen magnum decompression with expansile duraplasty. This patient had been asymptomatic for 14 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous investigators have examined a variety of techniques, both preoperative and intraoperative, to appropriately select patients for duraplasty . In a retrospective analysis of 82 consecutive cases of PFD with or without duraplasty, Yilmaz et al sought to associate preoperative MRI tonsillar ectopia measurements with postoperative outcome, retrospectively stratifying patients into three grades of cerebellar tonsillar descent.…”
Section: Discussionmentioning
confidence: 99%